On Ecological Esthetics of Nature - Łepko, Zbigniew (Studia Ecologiae et Bioethicae, 2005)
The Article presents postulates of ecological esthetics of nature according to human experience of ecological crisis taking into consideration threat of good mode of a person, who is described by sensory-emotional quality of his environment. According to this approach, ecological esthetics ought to be preceded by esthetics of nature which portrays human attitudes named „delight in nature”. The article presents also reconstruction of „history of esthetical concept of nature” which starts from Plato’s three: truth, good, and beauty. Therefore, paradoxically experience of ecological crisis forces: first – „rehabilitation of esthetics of nature” and second – postulate of „ecological esthetics of nature” as an answer on nowadays need of living in nature and with nature. It seems that in our time we more need nature than whenever before.